Next Generation On-Chip Networks: What Kind of Congestion Control Do We Need? - Nychis, George; Fallin, Chris; Moscibroda, Thomas; Mutlu, Onur (HotNets 2010: 9th ACM Workshop on Hot Topics in Networks, Monterey, California, 2010)
In this paper, we present network-on-chip (NoC) design and contrast it to traditional network design, highlighting core differences between NoCs and traditional networks. As an initial case study, we examine network congestion in bufferless NoCs. We show that congestion manifests itself differently in a NoC than in a traditional network, and with application-level awareness in the network to make proper throttling decisions we improve system performance by up to 28%. It is our hope that the unique and interesting challenges of on-chip network design can be met by novel and effective solutions from the networking community.